2009
DOI: 10.1007/s00425-009-0977-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the multiple polyadenylation signal AAUAAA on mRNA 3′-end formation and gene expression

Abstract: Polyadenylation (poly(A)) of eukaryotic mRNA is a critical step for gene expression. In plants, poly(A) signals leading to the formation of polyadenosine tails after mRNAs include the far upstream elements, the AAUAAA-like signals, and the mRNA cleavage sites for poly(A). Multiple AAUAAA signals leading to alternative polyadenosine formation have been found in many genes, but the effects of each AAUAAA signal on gene expression remain to be uncovered. A DNA fragment, whose transcript contains two canonical AAU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The constitutive cauliflower mosaic virus 35S (CaMV35S) promoters are most frequently utilized to enhance the expression of recombinant proteins in dicotyledons such as tobacco [48,56,57]. Polyadenylation sites downstream of the stop codon are critical for RNA processing; they also influence the stability of the transcript and the level of protein expression [58]. Widely used polyadenylation sites include those of the CaMV 35S transcript and the Agrobacterium NOS transcript [57,59].…”
Section: Peptide Purification and Antimicrobial Activity Evaluationmentioning
confidence: 99%
“…The constitutive cauliflower mosaic virus 35S (CaMV35S) promoters are most frequently utilized to enhance the expression of recombinant proteins in dicotyledons such as tobacco [48,56,57]. Polyadenylation sites downstream of the stop codon are critical for RNA processing; they also influence the stability of the transcript and the level of protein expression [58]. Widely used polyadenylation sites include those of the CaMV 35S transcript and the Agrobacterium NOS transcript [57,59].…”
Section: Peptide Purification and Antimicrobial Activity Evaluationmentioning
confidence: 99%
“…1). Polyadenylation is necessary for RNA processing, the stability of transcripts, and the level of protein expression 19 . For increasing the translation efficiency and improving the recombinant protein expression, codon optimization is very necessary 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Polyadenylation is necessary for RNA processing, the stability of transcripts, and the level of protein expression. 19 For increasing the translation efficiency and improving the recombinant protein expression, codon optimization is very necessary. 20 The Cecropin A is a peptide with an animal origin; therefore, its codons were optimized based on the codon usage of tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…Such a result could be viewed as two overlapping 6‐nt signals defining the same poly(A) site. A recent report found that the use of two AAUAAA signals in the same 3′‐UTR, but with different surrounding sequences, may result in differential expression levels of transcripts,38 which indicates that the strength of the signals can be modulated by adjacent signals such as FUE and CE (see below).…”
Section: Defining Poly(a) Sites In Plants and Algaementioning
confidence: 99%